Comparison of the Balance Performance of the Children with Spastic Cerebral Palsy before and after Exercise Therapy Program - Keyvan Sharif-Moradi; Nader Farah-Pour (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: This research is aimed to evaluate precisely a dynamic stability platform system to measure the center of gravity's sways around with fluctuations of cerebral spastic palsy children, before an after exercise therapy. Materials & Methods: Ten children with spastic diplegia cerebral palsy between 8 to15 years of age, wre participated in this quasi experimental (after - before) study. Their mean weight and height were (30.8kg ± 5.7kg) and (1.35m±0.09m) respectively. Subjects underwent a 12 weeks of exercise therapy. A dynamic stability platform system (BIODEX) was used to measure the center of gravity's sway around the center of base of support (COBOS). The balance tests were repeated on stable, almost stable and unstable base of support as well as with and without shoes. Results: Findings showed that the mean sway of center of gravity of the cerebral palsy children was significantly decrease after exercise therapy by 0.2 degrees (P=0.001). The greatest improvement achieved on AP directions in all conditions. Wearing shoes resulted in a significant decrease on the body sway. Conclusion: Exercise therapy significantly improved body balance in CP children. The function of the proprioceptives of the hip and trunk can be improved by exercise therapy and therefore should be considered in rehabilitation program.